2000
DOI: 10.1029/2000jd900300
|View full text |Cite
|
Sign up to set email alerts
|

Day‐to‐day temperature variability trends in 160‐ to 275‐year‐long European instrumental records

Abstract: Abstract. Day-to-day temperature variability is investigated in eight European series of daily mean temperatures beginning between 1722 and 183 3. Eight statistical measures of day-today temperature variability are compared. The intramonthly standard deviation of daily temperature anomalies is found to be a good measure. The absolute change in temperature anomaly from one day to the next is sensitive to changes in observational procedures and is suggested as a diagnostic tool for identification of inhomogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(66 citation statements)
references
References 30 publications
5
61
0
Order By: Relevance
“…In reality, we rather observe mixed and insignificant changes (e.g. see figure 1 in Karl et al (1995), figure 4 in Plummer (1996), figures 4, 5 and 8 in Moberg et al (2000) or figures 2-7 in Przybylak (2000a)). More recently Collins et al (2000) have found that most Australian stations studied revealed decreasing trends in maximum, minimum and mean temperature variability from 1957 to 1996.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reality, we rather observe mixed and insignificant changes (e.g. see figure 1 in Karl et al (1995), figure 4 in Plummer (1996), figures 4, 5 and 8 in Moberg et al (2000) or figures 2-7 in Przybylak (2000a)). More recently Collins et al (2000) have found that most Australian stations studied revealed decreasing trends in maximum, minimum and mean temperature variability from 1957 to 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of them focused on air temperature (e.g. Parker et al, 1992Parker et al, , 1994Karl et al, 1995;Plummer, 1996;Przybylak, 1996Przybylak, , 1999Przybylak, , 2000aMichaels et al, 1998;Jones, 1999;Collins et al, 2000;Moberg et al, 2000). Our knowledge during the last decade has grown significantly, but it is still far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…There are also several excellent records of daily surface air temperature (SAT) time series from the region extending over a similar period of time. Considerable evidence suggests that large-scale atmospheric circulation patterns are significantly correlated with multi-year and decadal SAT (Chen and Hellsr6m, 1999;Moberg et al, 2000) and ice conditions in the Baltic region (Jevrejeva, 2001). In average and mild winters, warm air masses associated with westerly moving cyclones from the Atlantic dominate the Baltic climate.…”
Section: Introductionmentioning
confidence: 99%
“…At all meteorological stations temperature oscillations are highly variable, warming and cooling trends often alternating. Moreover, our analysis shows a slight decrease in temperature variability, which is common in many SAT series of the Northern Hemisphere (Karl et al, 1995;Moberg et al, 2000;. Figure 6 shows the interannual variation and trend of the average temperature for the Florence and Genoa time series.…”
Section: Sat Datamentioning
confidence: 99%